Sistem Informasi Pengarsipan Surat Keluar Masuk di Kantor Camat Teluk Nibung Kota Tanjungbalai - Agrinda Aulia Lubis; Bambang Irwansyah (Merkurius : Jurnal Riset Sistem Informasi dan Teknik Informatika, 2025)
This study describes the development of a web-based Archival Information System aimed at improving the efficiency and accuracy of managing incoming and outgoing correspondence at the Teluk Nibung Sub-District Office in Tanjungbalai City. The system enhances administrative workflows by digitizing key processes, including the receipt, verification, recording, and archiving of incoming letters, as well as the preparation and distribution of outgoing letters. Management of incoming and outgoing documents is handled separately to ensure systematic processing and to reduce errors commonly found in manual administration. Developed using web-based technologies and supported by a MySQL database, the system enables flexible access, automated data storage, and faster document retrieval. The implementation results indicate notable improvements in administrative performance, such as quicker processing times, reduced reliance on paper-based archives, and improved data security. Overall, the system supports the modernization of public sector administration and contributes to more effective, reliable, and sustainable archival management practices at the sub-district office level.